Particle flux in the twilight zone of the eastern Indian Ocean: A constraint from 234U– 230Th and 228Ra– 228Th disequilibria - Okubo, Ayako; Obata, Hajime; Luo, Shangde; Gamo, Toshitaka; Yamamoto, Yoshiyuki; Minami, Hideki; Yamada, Masatoshi (Deep-sea research. Part I, Oceanographic research papers, 2007)
Total 230Th and 228Th vertical distributions were measured in the eastern Indian Ocean. Based on disequilibria of 234U– 230Th and 228Ra– 228Th, we estimated the particle flux from the surface to 950 m. The estimated particle flux ranged from 190±60 (150 m in the Southern Ocean) to 8.4±2.5 mg/m 2/day (950 m in the West Australian Basin). The particle fluxes correlate well with estimates of nitrate supply by vertical mixing to the euphotic zone, suggesting local control by new production. Flux attenuation at mesopelagic depths appears to be related to biogenic carbonate and silica remineralization based on comparison to alkalinity and dissolved silicate distributions, with possible additional control by lithogenic particle inputs. The particle flux estimates obtained by combining the 234U– 230Th and 228Ra– 228Th disequilibria offer advantages over those from 228Ra– 228Th disequilibrium alone, in that they can account for some aspects of vertical mixing and thus are applicable to a wider range of oceanographic settings.